Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10071375
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antioxidant and Sperm Viability of Nelumbo nucifera Petal Extracts

Abstract: Sacred lotus (Nelumbo nucifera Gaertn.; N. nucifera) is a common ingredient in traditional medicine and Thai recipes. Its petal is an agricultural waste from stamen production. There are limitations in the used and pharmacological data of the petals resulting in more petals waste. The aims of this study were to investigate the phytochemical contents, antioxidant activity, and potential effects on sperm viability of aqueous (NAE) and ethanolic extracts (NEE) of both red and white N. nucifera petals. The white N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 37 publications
(57 reference statements)
4
38
1
Order By: Relevance
“…The results of this study differed from a previous study in that testicular and epididymis weight increased after treatment with hexane M. oleifera extracted in male mice [45]. Type of solvent in extraction affected the amount of phytochemical contents, for example, N. nucifera petals extracted with hot water had higher phytochemical contents than 95% ethanol [29]. Therefore, the method of solvent extraction and the species of animal might have an effect on testicular weight in the animal model [45].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The results of this study differed from a previous study in that testicular and epididymis weight increased after treatment with hexane M. oleifera extracted in male mice [45]. Type of solvent in extraction affected the amount of phytochemical contents, for example, N. nucifera petals extracted with hot water had higher phytochemical contents than 95% ethanol [29]. Therefore, the method of solvent extraction and the species of animal might have an effect on testicular weight in the animal model [45].…”
Section: Discussioncontrasting
confidence: 96%
“…It contains essential phytochemical compounds, especially total phenols and flavonoids. Phenolic compounds were easily eluded by polar solvent [27,28], as reported in the study on the N. nucifera petal extract [29]. In the present study, the phenolic compounds eluded in water were shown to be at a higher concentration than flavonoids.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These effects were the same as taking Vit E, as is commonly used as a positive control, because it is an effective antioxidant for deceased oxidative stress, preventing cell damage, and increasing sperm quality in frozen sperm and azoospermia samples [10,27,28]. The present study showed the WNAE enhanced the sperm motility, normal sperm morphology, sperm viability, and acrosome integrity during the oxidative stress process, suggesting that the crude extract in WNAE contains bioactive compounds that might act with direct effect on the scavenging process of the free radicals in cattle sperm induced by MZ, which was similar to the study in rat sperm induced by ferrous sulfate heptahydrate (FeSO 4 ) [5]. Therefore, the compounds of WNAE also have a benefit effect against cell damage.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the high economic demand for stamens, the lotus petals become agricultural waste. The phytochemical study using a high-performance liquid chromatography (HPLC) method found that the petals of N. nucifera contained phytochemical components, including quercetin, gallic acid, catechin, and p-hydroxybenzoic acid, as well as the white N. nucifera petals aqueous extraction (NAE) which had enhanced rat sperm viability, more phytochemical and antioxidant activity properties than red NAE [5]. However, there are no reports of white NAE for use against mancozeb (MZ) toxicity.…”
Section: Introductionmentioning
confidence: 99%